Efeitos do exercício físico no sono de pacientes com insônia crônica primária - Passos, Giselle Soares [UNIFESP] (2008)
Some evidences suggest that physical exercise can improve sleep quality of insomniac patients. The aim of this study was to evaluate and compare the acute effect of three modalities of physical exercise in anxiety state and in the sleep quality in insomnia patients. Thirty-six patients (8 men and 28 women) with primary chronic insomnia (mean age 44,4 ± 8) were selected to participate of the study. Two methods were used to evaluate sleep quality; sleep log and polysomnography, after a night of laboratory adaptation. IDATE-State questionnaire was used to evaluate anxiety state. The protocol included three experimental groups (moderate aerobic exercise - MAE, n = 9, heavy aerobic exercise - HAE, n = 9, moderate strength exercise - MSE, n = 9) and a control group (CTL, n=9). EAM group realized exercise on a treadmill in the intensity of ventilatory threshold 1 (during 50 continuous minutes). EAI realized exercise on a treadmill in the intensity of ventilatory threshold 2 (three periods of 10 minutes of exercise alternating with 10 minutes of rest). ERM realized 3 sets of 10 repetitions at 50% of 1 RM were performed in shoulder press, chest press, vertical traction, leg press, leg curl, leg extension, abdominal crunch e lower back. The polysomnographic results showed reduction in the sleep onset latency - SOL (54%) and in the wake time - WT (36%), increase in total sleep time – TST (21%) and in the sleep efficiency - SE (18%) in the MAE group, after exercise session. Significant increase in the TST (37%) and reduction in the SOL (40%) were observed In the sleep log of volunteers of the group MAE. Finally, a significant reduction (7%) In the anxiety state was also observed after moderate aerobic exercise session. The results suggest that an acute session of moderate aerobic 73 exercise, but not heavy aerobic or moderate strength exercises, can reduce the anxiety state and improve the sleep quality of insomnia patients.